IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA - Yusuf, M; Handriadi, Handriadi; Andini, Riddo; Nabila, Auzia Fiska (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2024)
This research was motivated by one of the changes brought about in the independent learning policy. In terms of pedagogy, the independent learning policy will abandon the standardization approach towards a more complete heterogeneous approach that enables educators and students to explore the treasures of knowledge that continue to develop. State Vocational School 4 Kota Pariaman is one of the schools that has implemented the independent learning curriculum since July in the 2022/2023 academic year. The aim of this research is to find out the planning, implementation and obstacles to the independent learning curriculum in Islamic Religious Education subjects in class X of SMK Negeri 4 Kota Pariaman. The research method used is descriptive qualitative field research. The results of this research showed that planning for the independent learning curriculum started with outreach activities carried out by the school principal to educators. Implementation will start in the 2022/2023 academic year and will only be implemented in class X with a total of approximately 150 students. The obstacle encountered is the lack of facilities and infrastructure in schools so that educators are required to be creative in the learning process